Financial Sector Assessment Program : Malaysia - Core Principles for Effective Deposit Insurance Systems - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
This assessment of compliance with the Core Principles for Effective Deposit Insurance Systems (Core Principles) was conducted as a part of the Financial Sector Assessment Program (FSAP) performed by the International Monetary Fund and the World Bank at the request of the Malaysian government. This assessment was conducted by Claire McGuire, Senior Financial Sector Specialist with the World Bank, during a mission to Malaysia from March 27 to April 13, 2012. The assessment was based on a review of relevant laws, regulations and regulatory and supervisory practices related to the conventional banking sector and the operations of PIDM. There has been no experience with bank failures in Malaysia since Perbadanan Insurans Deposit Malaysia (PIDM's) establishment in 2005. As a result the assessment looked at the relevant provisions of the legal framework without consideration of how the laws had been applied in practice or interpreted by the courts. Several weaknesses in the legal framework have been noted in this assessment.